Los santos peruanos dominicos como personajes literarios en las tradiciones de Ricardo Palma - Rodríguez Chávez, Iván (2018)
This study explains the addition of two Peruvian Dominican Saints: Saint Rose of Lima and Saint Martin de Porres as literary characters in the Traditions of Ricardo Palma. The author portrays them in their human dimension, tied to their ordinary and humble daily chores. The tradition is a brief narrative, written in a colloquial form of the language, with a humorous background scattered throughout the text, yet focused on some sections of it. They were chosen because of their roots to the people, how appealing they are to the reader, in aspects of their lives defined as secular literature.